The Relationship between of Moral Injury and Radicalisation: A Systematic Review. (2nd November 2022) - Williamson, Victoria; Murphy, Dominic; Stevelink, Sharon A.M.; Jones, Edgar; Allen, Shannon; Greenberg, Neil
Abstract: This review aimed to explore individual-level factors involved in radicalization and the impact of moral injury on an individual's beliefs and behaviors that are relevant to radicalization. The results indicate that both individuals who develop radical beliefs and those with moral injury are exposed to events which provoke similar adverse outcomes, including a loss of personal significance, suggesting that moral injury could be a useful way to understand the process of radicalization. Understanding the processes involved in moral injury may inform preventative programs, as well programs to promote disengagement from radical action in those who have already been radicalized.